Sunitinib with concomitant radiation therapy in inoperable sarcomas: Final results from the dose escalation and expansion parts of a multicenter phase I study. (March 2022) - Sunyach, Marie-Pierre; Penel, Nicolas; Montané, Laure; Cassier, Philippe A.; Largo, Abel Cordoba; Sargos, Paul; Blanc, Ellen; Pérol, David; Blay, Jean-Yves
Highlights: RT-SUTENT assesses continuous sunitinib 37.5 mg with exclusive RT in sarcoma. The follow-up was 19.5 (14-36.5) months; median PFS was 6.5 (1.9-31.1) months. Median OS was not reached. At 6 months, L-PFR was 73.3% (95%CI 44.9-92.2%). Sunitinib 37.5 mg combined with exclusive RT was found feasible, efficient. The use of more recent MKI combined with RT need to be further investigated. Abstract: Introduction: Local control in sarcoma is rarely achieved with exclusive radiotherapy (RT). We aim to assess the feasibility and safety of sunitinib continuously administrated with concomitant RT in inoperable non-GIST sarcomas patients. Methods: This multicentric French 3 + 3 dose escalation study included patients with inoperable locally advanced or recurrent sarcoma, ECOG-PS <2, ≤2 metastatic sites and no brain metastases, adequate organ functions and absence of uncontrolled hypertension, who had never received sunitinib or radiotherapy. The escalation phase planned to use sunitinib dose levels (DL1: 25; DL2: 37.5; DL3: 50 mg/day) with standard RT (60 Gy, 30 fractions, 5 fractions/week/6 weeks). The primary endpoint was to determine the incidence of dose-limiting toxicities (DLT) in the first 14 weeks and the maximal tolerated dose (MTD). Secondary endpoints included safety (acute and late toxicities), local control at 6 months including local progression free rate (L-PFR) progression free survival (PFS), overall survival (OS), proportion of patients eligible for surgery after treatment. Results: From May 2011 to April 2016, the dose-escalation phase enrolled 10 patients (DL1 N = 4; DL2 N = 6). No DLT was observed in at DL1. One DLT (grade 4 thrombopenia) occurred at DL2. The 19 patients treated at DL2 (including the 13 patients from the expansion phase) received sunitinib for a median duration of 42.7 (2.8–79.1) days, and radiotherapy for 6.4 (1–8) weeks; all but 3 patients received 60 Gy (40 Gy, early progression ( N = 1); 8 Gy, early death ( N = 1), prescribed dose, 50 Gy ( N = 1)). With a median follow-up of 19.5 (14–36.5) months, the median PFS was 6.5 (1.9–31.1) months. Median OS was not reached. At 6 months, L-PFR was 73.3% (95%CI 44.9%-92.2%). One patient was amendable to surgery after treatment. Sunitinib-related grade ≥ 3 adverse events occurred in 58% of the patients treated at DL2 (Escalation N = 4; Expansion N = 7). Seven (36.8%) deaths related to disease progression were reported. Conclusion: This is the first trial assessing the combination of continuous administration of sunitinib 37.5 mg with exclusive RT in non-GIST sarcoma. Whereas this combination was found feasible, efficient, further investigations of combinations of more recent multikinase inhibitors with RT need to be explored.